Intermediate to advanced SQL : move beyond the basics to master complex concepts - Taylor, Allen (Apress, 2018)
"Learn the basics of creating, maintaining, protecting, and querying relational databases using SQL, the standard language used to communicate with all relational databases. Building on the author's previous course, Beginning SQL, SQL expert Allen Taylor provides five more lessons to continue your journey to mastery of one of the most important topics in IT. This video course guides you step-by-step in the design, creation, and operation of databases, using graphics, animation, and audio commentary to reinforce concepts and enhance learning. Intermediate to Advanced SQL covers complex data models, making highly selective retrievals, and grouping and ordering results. You'll also learn how to use multi-table queries, and to protect your data from mistakes or hacking attempts. After watching the course, along with the previous course, you will have a solid foundation in SQL and be able to apply it to any relational database."--Resource description page